Analisis Putusan Pengadilan dalam Sengketa Perjanjian yang Disebabkan oleh Wanprestasi : Putusan PT PALEMBANG Nomor 68/PDT/2016/PT PLG - Denanda Zahra Ajrina; Marcha Jeanne Mawene; Bagas Jeremia Siahaan; Naumy Syauqina Dalida; Sulastri Sulastri (Journal of Student Research, 2025)
Default is a violation of an agreement which can give rise to various legal problems. This research aims to carry out a comprehensive analysis of court decisions in cases of breach of contract PT PALEMBANG Court Decision Number 68/PDT/2016/PT PLG, it is hoped that this research can provide a deeper understanding of the court mechanism in influencing the assessment of the existence of elements of bad faith in the default case and the difference in legal treatment between total and partial default in the PT PALEMBANG decision Number 68/PDT/2016/PT PLG. Apart from that, it is also hoped that this research can provide recommendations for legal practitioners and parties involved in agreements to avoid default in the future.